Polskie frazeologizmy w słoweńskich przekładach wierszy Wisławy Szymborskiej - Baran, Katarzyna (Przekłady Literatur Słowiańskich, 2012)
Polish idioms in Slovenian translations of Wislawa Szymborska poems Idioms are often used in polish poetry. Due to their expressiveness and vulnerability for linguistic operations they are subject to different language games. Szymborska often uses transformation of idioms such as: contamination, removing of element, substitution. In her poetry idioms and their modifications are carriers of irony and jokes, they allow to preserve the intellectual and emotional distance restraint. Translation of idioms is problematic because of their expressiveness, symbolic recognition of world and ambiguity. In idioms is hidden a linguistic picture of world, which requires discovery and interpretation by an translator. Vast majority of idioms and their transformations occurring in the poems of Wislawa Szymborska has its own equivalents. In the case they doesn’t have their own equivalents, translators uses following techniques: free combination of words, tracing, amplification. These techniques causes changes in vocabulary and style, but they doesn’t affect the quality of translation. These changes are related to collision of Polish and Slovenian culture, which causes language and cultural Barriers. Language barriers relate to systemic differences between the languages, are especially noticeable in vocabulary and syntax. Cultural barriers are associated with different degree of influence of German and French culture into Poland and Slovenia, and the expression of irony. The role of the interpreter is to mediate between two cultures, and establish methods to overcome cultural and linguistic barriers. Key words: idioms, poetry, translation, transformations of idioms, Wislawa Szymborska.